In-Vitro Effect of Alcohol and Non-Alcohol Mouthwash on Color Change of Two Types of Bleach Shade Composite - N Nasoohi; M Hadian; M hoorizad; SS Hashemi; SH Naziri saeed (Islamic Azad University, 2019)
Background and Aim: The purpose of this study was to examine the effect of alcohol and non-alcohol mouthwashes on the color change of two types of bleach shade composite. Materials and Methods: Twenty-two samples of IPS empress direct composite (Ivoclar Vivadent, Schaan, Liechtenstein) and 22 samples of Vitalescence snow white composite (Ultradent Products, South Jordan, UT, USA) were prepared in 10 mm diameter and 2 mm thickness. The specimens were polished with Sof-Lex (3M ESPE, USA) abrasive papers in supra fine, fine, and medium sizes. The specimens were then stored for 24 hours in distilled water at 37°C, and an initial colorimetric assay was performed using SP64 spectrophotometer. Samples were randomly divided to be placed in 20 ml of alcohol and non-alcohol Listerine mouthwashes and were incubated at 37°C for 24 hours. The color of the specimens was again measured, and color change (ΔE) was calculated. Data were analyzed using two-way analysis of variance (ANOVA) at 95% confidence level. Results: None of the mouthwashes caused clinically significant discoloration in the samples. The effect of both mouthwashes on composite discoloration was statistically significant (P=0.0001), and the interaction between the mouthwash and type of restorative material was significant (P=0.0001). Conclusion: According to the findings of this study, alcohol mouthwashes cause more discoloration in composite resins.